The affection of plasma exosomes on airway obstruction and endothelial function in OSA patients - Li, Lin; Wang, Qing; Xin, Wenshu; Wen, Kaixue; hang, Yuhao Z (Cellular and Molecular Biology, 2022)
This study aimed to investigate the effects on airway obstruction and endothelial function by extracting and analyzing plasma exosomes with OSA patients. For this purpose, the clinical data and imaging data of 60 patients with OSA were retrospectively analyzed, who were admitted to the Central Hospital from Apr．2018 to Jul．2021．By using an electron microscope for the observation of exosomes, the degree of airway obstruction was compared by pulmonary function instrument, and HE staining was performed to analyze them. The results showed that the diameter of exosome particles was concentrated at 80.5 ~ 158.6 nm, the diameter of OSA exosomes was concentrated at about 121.9 nm, and the diameter of exosomes in the control group was concentrated at about 145.0 nm. Compared with the patients in the control group, the level of miRNA-33b-3p in the control group was significantly different (P < 0.05). The content of exosomal miRNA-33b-3p in OSA patients decreased significantly, and the corresponding airway obstruction increased. The results of HE staining showed that there were obvious atherosclerotic plaques in the arterial endothelium of the OSA group, and the atherosclerotic plaques were significantly reduced after miRNA-33b-3p injection (P < 0.05). In general, OSA patients can regulate airway obstruction and endothelial cell function by controlling the expression of Plasma exosomes and miRNA-33b-3p, resulting in increased airway obstruction and endothelial cell atherosclerosis.